PERHITUNGAN TINGKAT ENERGI SUMUR POTENSIAL KEADAAN TERIKAT MELALUI PERSAMAAN SCHRODINGER MENGGUNAKAN METODE BEDA HINGGA - Hanifah Rahmayani (PILLAR OF PHYSICS, 2014)
Schrodinger equations are widely used in solving a variety of problems, one of them is particles in a box in especially of potential wells bound state. Particle in a box is a discrete circumstances, so we must examined whether or not the degeneration of these particles. The Schrodinger equation analysed to get a form of modeling of energy levels and wave functions in potential wells of the circumstance used numerical method. We also can show energy level of each state from the model. The numerical approaches is finnite difference method using  Matlab R2010 software. Numerical calculation shows k value. k1 and k3 gets from solution of cos equation, whereas k2 and k4 gets from solution of sin equation. The k value is used to know the energy level in potential wells. energy level model show wave fucntion. In potential well bound state, Energy level and wave functions be smaller when potential energy is high and it is high when potential when potential energy is small. When wide of potential well is smaller, energy level and wave function be smaller too. But there isn’t show energy level and wave function when wide of potential well is high. The shape of energy level and and wave function of particle in box.